Pengaruh Kecerdasan Emosional, Sarana Dan Prasarana, Kebiasaan Belajar, Dan Gaya Hidup Terhadap Motivasi Belajar Siswa Kelas XI SMA Negeri 1 Lengayang Tahun Ajaran 2022/2023 - Okvoti, Isla Citra; Pratama, Indra Mulia; Erita (Yayasan Pendidikan Tanggui Baimbaian, 2023)
This type of research is descriptive and associative research. The population of this study was XI SMA Negeri 1 Lengayang, which consisted of 96 students. The sampling technique used Proportional Random Sampling with a total sample of 74 students. Data analysis used multiple linear regression analysis and hypothesis testing used the t test and f test. The analysis was assisted by the SPSS version 22 program. Based on the results of the research, it can be explained that: there is a positive and significant influence of emotional intelligence (X1) on the learning motivation of class XI students of SMA Negeri 1 Lengayang. It is known that the tcount is 2.312 >ttable is 1.66571 with a significant value of 0.024 < α = 0.05 means There is no positive and significant effect of facilities and infrastructure (X2) on the learning motivation of class XI students of SMA Negeri 1 Lengayang. It is known that the tcount is 1.400 >ttable is 1.66571 with a significant value of 0.166 < α = 0.05 means There is a positive and significant influence between Study Habits (X3) on the learning motivation of class XI students of SMA Negeri 1 Lengayang. It is known that the tcount value is 2.755 <ttable is 1.66571 with a significant value of 0.008 < α = 0.05 means. There is no influence between lifestyle (X4) and does not have a positive and significant effect on the learning motivation of class XI students of SMA Negeri 1 Lengayang.